Iron–Sulfur Cluster Biogenesis and Iron Homeostasis in Cyanobacteria - Gao, Fudan (Frontiers in Microbiology, 2020)
Iron-sulfur (Fe-S) clusters are ancient and ubiquitous cofactors and are involved in many important biological processes. Unlike the non-photosynthetic bacteria, cyanobacteria have developed the sulfur utilization factor (SUF) mechanism as their main assembly pathway for Fe-S clusters, supplemented by the iron-sulfur cluster (ISC) and nitrogen-fixing (NIF) mechanisms. The SUF system consists of cysteine desulfurase SufS, SufE that can enhance SufS activity, SufBC2D scaffold complex, carrier protein SufA, and regulatory repressor SufR. The S source for the Fe-S clusters assembly mainly originates from L-cysteine, but the Fe donor remains elusive. This mini-review mainly focuses on the biogenesis pathway of the Fe-S clusters in cyanobacteria and its relationship with iron homeostasis. Future challenges of studying Fe-S clusters in cyanobacteria are also discussed.